2014
DOI: 10.4238/2014.july.24.24
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary intake of folate and MTHFR genotype with breast cancer risk

Abstract: ABSTRACT. We conducted a hospital-based case-control study to investigate the associations of dietary intake of folate and MTHFR C677T and A1298C polymorphisms with breast cancer in a Chinese population. A 1:1-matched case-control study was conducted. Two hundred and thirty patients who were newly diagnosed and histologically confirmed breast cancer and 230 controls were enrolled from Xinxiang Central Hospital. Folate intake was calculated by standard portion size and relative size for each food item in the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
2
9
0
Order By: Relevance
“…In our study, MTHFR C677T and MTR A2756G polymorphisms played an important role in breast cancer risk, and had interactions with folate, vitamin B 6 , and vitamin B 12 intakes. Our findings are consistent with those of several previous studies in China [11,16,31,32]. Wang et al conducted a 1:1 matched case-control study with 230 cases and 230 agematched controls and found that TT genotype and T allele of MTHFR C677T had an increased risk of breast cancer when compared with CC genotype [31].…”
Section: Discussionsupporting
confidence: 95%
“…In our study, MTHFR C677T and MTR A2756G polymorphisms played an important role in breast cancer risk, and had interactions with folate, vitamin B 6 , and vitamin B 12 intakes. Our findings are consistent with those of several previous studies in China [11,16,31,32]. Wang et al conducted a 1:1 matched case-control study with 230 cases and 230 agematched controls and found that TT genotype and T allele of MTHFR C677T had an increased risk of breast cancer when compared with CC genotype [31].…”
Section: Discussionsupporting
confidence: 95%
“…Several studies have also reported an association between polymorphisms in the MTHFR gene and breast cancer risk (He et al, 2014;Rai, 2014;Wang et al, 2014). Wang et al (2014) discovered an association between MTHFR C677T polymorphisms and increased risk of breast cancer in a case-control study with 230 patients and control subjects each.…”
Section: Discussionmentioning
confidence: 98%
“…Previous epidemiological studies have reported that single nucleotide polymorphisms in the candidate genes could contribute to cancer risk. Many studies have reported an association between the MTHFR 677C/T and 1298A/C gene polymorphisms and susceptibility to breast cancer (He et al, 2014;Rai, 2014;Wang et al, 2014;López-Cortés et al, 2015); however, these results are inconsistent because of the small sample size used. In our study, the TT genotype of MTHFR 677C/T was found to be associated with an increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations